Psycometric Validation of an Instrument to Measure Person-Centred Teamwork in Hospital Settings - Alida Viljoen; Ronell Leech; Paul Slater; Andries Masenge; Tanya Heyns (Nursing Research and Practice)
Link to Practice: The 38 item person-centred teamwork instrument indicated good fit for measuring the constructs, and the instrument was validated. Each of the items was reliable for measuring person-centred teamwork. The instrument can be applied internationally to assist in the measurement of person-centred teamwork practices to improve clinical outcomes.